Predictors of survival outcomes in sinonasal squamous cell carcinoma: an analysis of the National Cancer Database. Issue 6 (23rd November 2020) - Farrell, Nyssa Fox; Mace, Jess C.; Detwiller, Kara Y.; Li, Ryan; Andersen, Peter E.; Smith, Timothy L.; Clayburgh, Daniel R.; Geltzeiler, Mathew
Abstract : Background: Sinonasal squamous cell carcinoma (SNSCC) is a rare malignancy that poses management challenges. Although surgery and chemoradiation therapy (CRT) remain therapeutic mainstays, induction chemotherapy (IC) has emerged as a useful adjunct with locally advanced disease. This study used the National Cancer Data Base (NCDB) to examine treatment outcomes for patients diagnosed with SNSCC. Methods: The NCDB (2004‐2015) was queried for cases with SNSCC. Multivariate hazard regression modeling was used to identify significant predictors of 24‐month and 60‐month overall survival (OS) including treatment modality. Results: A total of 3516 patients with SNSCC met inclusion criteria, including 1750 patients (49.8%) treated with surgery ± adjuvant therapy, 1352 (38.5%) treated with definitive radiotherapy (RT) or CRT, 300 (8.5%) who underwent IC followed by definitive CRT, and 114 (3.2%) who received IC followed by surgery and adjuvant therapy. Hazard modeling for confirmed treatment modality significantly associated ( p < 0.001) with OS after adjustment. Patients who received surgical intervention ± adjuvant therapy had lower 24‐month and 60‐month mortality risk compared to definitive RT or CRT (hazard ratio [HR] ≥ 1.97; p < 0.001) or IC followed by definitive CRT (HR ≥ 1.73; p < 0.001). Compared to primary surgery ± adjuvant therapy, patients undergoing IC then surgery had similar 24‐month and 60‐month OS ( p ≥ 0.672) after adjustment. Conclusion: Multimodality therapy, including surgical intervention, associates with improved OS after multifactorial adjustments. IC followed by surgery associated with improved OS compared to IC, followed by CRT and CRT alone. Study results highlight the utility of surgery toward optimizing OS in patients with SNSCC and demonstrates the potential utility of IC when primary surgical management is not preferred.